Si fa gong bao (Guo jia tu shu guan chu ban she, 2011)
"Judicial Gazette," a collection of 1912 -1948, published in the Official Gazette of the Ministry of Justice and the Judicial Yuan. 88 hardcover 16, photocopying published.